The effect of age and sex on the racing pace in the marathon in relation to finish time - Mádyová, A. (Mazarykova Universität, 2017)
This study discusses how the racing pace in the marathon is influenced by age and sex. Male and older runners are better pacers. This topic should be further researched as it may be of great help to achieve better overall results in marathon racing. To set and train the proper velocity can play a key role for improvement of performance mainly for younger runners as they tend to exceed their limits by running faster at the beginning.